Alkaloid diversity expansion of a talent fungus Penicillium raistrichii through OSMAC-based cultivation - Zhong, Meijia; Kang, Huihui; Liu, Weizhong; Ma, Liying; Liu, Desheng (Frontiers in Microbiology, 2023)
Alkaloidal natural products are attractive for their broad spectrum of pharmaceutical bioactivities. In the present work, the highly productive saline soil derived fungus, Penicillium raistrichii, was subjected to the strategy of OSMAC (one strain many compounds) with changes of cultivation status. Then, the work-flow led to the expansion of the alkaloid chemical diversity and subsequently induced the accumulation of three undescribed alkaloids, named raistrimides A-D (1-4), including three β-carbolines (1-3), one 2quinolinone (4), and one new natural product, 2-quinolinone (5), along with six known alkaloid chemicals (6-10). A set of NMR techniques including 1 H, 13 C, HSQC and HMBC, along with other spectroscopic data of UV-Vis, IR and HRESIMS, were introduced to assign the plain structures of compounds 1-10. The absolute configuration of 1-3 were elucidated by means of X-ray crystallography or spectroscopic analyses on optical rotation values and experimental electronic circular dichroism (ECD) data. In addition, it was the first report on the confirmation of structures of 6, 7 and 9 by X-ray crystallography data. The microbroth dilution method was applied to evaluate antimicrobial effect of all compounds towards Staphylococcus aureus, Escherichia coli and Candida albicans, and the results indicated compounds 1, 3 and 4 to be bioactive, which may be potential for further development of anti-antimicrobial agents. It proved that OSMAC strategy was a powerful and effective tool in search of new chemical entities from talent fungi.